Synthesis and Evaluation of 2‐Alkylthio‐4‐(N‐substituted sulfonamide)pyrimidine Hydroxamic Acids as Anti‐myeloma Agents. (10th December 2015) - Xiang, Jinbao; Leung, Crystal; Zhang, Zhuoqi; Hu, Cassie; Geng, Chao; Liu, Lili; Yi, Lang; Li, Zhiwei; Berenson, James; Bai, Xu
Abstract : A series of pyrimidine hydroxamic acids with a sulfide substituent at the second position and a sulfonamide substituent at the fourth position have been synthesized and evaluated for their activity against human myeloma cell line RPMI 8226. Several compounds exhibited significant anti‐cancer potency. It was found that representative compound6a selectively killed cancerous but not normal cells. Moreover, compound6a was effective in causing apoptosis in RPMI 8226 cells and exhibited promising HDAC‐inhibitory activities. Abstract : A series of pyrimidine hydroxamic acids with a sulfide substituent at the 2‐position and a sulfonamide substituent at the 4‐position have been synthesized and evaluated for their activity against human myeloma cell line RPMI 8226. It was found that representative compound6a selectively killed cancerous but not normal cells. Moreover, compound6a was effective in causing apoptosis in RPMI 8226 cells and exhibited promising HDAC‐inhibitory activities.